Droughts in Pakistan: A spatiotemporal variability analysis using the standardized precipitation index - Xie H; Ringler, Claudia; Zhu, T.; Waqas A (Informa UK Limited, 2013)
We investigated the spatiotemporal variability of drought incidence in Pakistan during 1960–2007 by calculating Standardized Precipitation Index fields for 3-, 6- and 12-month scales using gridded precipitation data. Principal component analysis revealed that droughts are wide-spread and often occur simultaneously over large areas. Furthermore, spectral analysis identified a 16-year drought recurrence period. Three such drought-intensive periods were identified: the late 1960s to early 1970s; the middle 1980s; and the late 1990s to early 2000s. Hence, drought patterns need to be integrated into long-term water planning as well as emergency preparedness.